Tariqilabeo iranicus, a new species of labeonine fish from the Makran basin in Iran (Teleostei: Cyprinidae) - Esmaeili, Hamid Reza; Sayyadzadeh, Golnaz; Masoumi, Amir Hassan; Hashemi, Seyed Hassan; Echreshavi, Sorour (Zootaxa, 2025)
A new species of labeonine fish, Tariqilabeo iranicus sp. nov. is described from the Makran drainage basin of Iran. It is distinguished from its closest congener, Tariqilabeo diplochilus, by having a silvery spot on the operculum, and a snout shorter than the postorbital length. It is further distinguished from its congeners by a combination of characters: 34–36 lateral-line scales, 11–14 predorsal scales, 22–24 total gill rakers on the first branchial arch, 3+8 ½ dorsal-fin rays, 14–16 pectoral-fin rays, 9 pelvic-fin rays, 3+5½ anal-fin rays, 2–3 scales between anal-fin origin and anus, 7–8 scales between posteriormost pelvic-fin base and anus, 2 pairs of small barbels, presence of fringes on the rostral fold, and absence of horny tubercles on snout and cheek in males. Tariqilabeo iranicus sp. nov. is further distinguished from T. diplochilus by a K2P nearest-neighbor distance of 4% in the COI barcode region. A key to the species of Tariqilabeo is also presented.